ChemInform Abstract: Amine‐Catalyzed Asymmetric Cross‐Aldol Reactions Using Heterofunctionalized Acetaldehydes as Nucleophiles. Issue 29 (22nd July 2014) - Kano, Taichi; Sakamoto, Ryu; Maruoka, Keiji
Abstract Both syn‐ and anti‐difunctionalized compounds can be obtained from the same set of reactants by replacing the catalyst.